Cognitive Activation in the Mathematics Classroom and Professional Competence of Teachers
VI, 378 p.
Keywords: Cognitive Activation in the Mathematics Classroom and Professional Competence of Teachers presents the findings of the Professional Competence of Teachers, Cognitively Activating Instruction, and Development of Students´ Mathematical Literacy project (COACTIV). COACTIV applies a broad, innovative conceptualization of teacher competence to examine how mathematics teachers’ knowledge, beliefs, motivational orientations, and self-regulation skills influence their instructional practice and teaching outcomes. Moreover, it gauges the effects of these teacher characteristics on student learning, as indexed by the progress of students in each class. For this book, COACTIV study data relating to various aspects of teacher competence and classroom instruction from the perspective of both the teachers themselves and their students was collected and analyzed. Questions addressed and discussed include: What are the characteristics of successful teaching? What distinguishes teachers who succeed in their profession? How can the quality of instruction be improved? Written for researchers from a broad range of areas, such as educational psychology, general education, and mathematics education, this book effectively demonstrates how teacher competence relates directly to measurable student learning gains.